Literature Review : Determination Of Microplastic Content In Seafood? - Rezka Rahmadhana; Tri Joko; Nikie Astorina (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Microplastics is a plastic particle with a diameter less than 5mm. Seafood that has been contaminated by microplastics is not safe for consumption because it can cause detrimental biological effects. The objective of this research is to provide an overview regarding the identification of contaminated microplastics in seafood. This Research used the literature review method with the object of research in the form of fish and bivalves originating from the sea. Articles were inquired from 6 online databases, which are Google Scholar, Garba Rujukan Digital (Garuda), Science Direct, Scopus, JSTOR, and EBSCO Host. Articles that are used in this research have an observational research method. There are 7 articles were found for this research. As much as 421 microplastics particle was found in bivalves and 386 particle in fish. The highest microplastics type found is fiber, which contaminates 90.7% of fish and 86% of bivalves. The type of microplastics that are generally found in the digestives system in seafood are fiber and fragment.Keywords : Microplastic, Seafood, Fiber